First principles DFT calculations of the optical properties of A4BX6 group crystals - Ilchuk, H.; Solovyov, M.; Lopatynskyi, I.; Honchar, F.; Tsyupko, F. (Physics and Chemistry of Solid State, 2021)
The results of investigating of the electron band energy structure and optical properties of A4BX6 (Tl4HgI6 and Tl4CdI6) group crystals are presented. The energy band structures of Tl4HgI6 and Tl4CdI6 crystals are calculated from the first principles within generalized gradient approximation (GGA). The band structure and reflection index were calculated using a pseudopotential method in the framework of density functional theory. Optical absorption edge in Tl4HgI6 and Tl4CdI6 is formed by direct optical transitions. The spectral dependence of the reflection index was calculated on the basis of the energy band results with using the Kramers–Kronig method. The spectra show pronounced anisotropy in E||a(b) and E||c polarizations. It was found the anomalous by large values of the birefringence (Δn > 0.18 for Tl4HgI6 and Δn > 0.03 for Tl4CdI6) in the visible and near infrared region.